2009
DOI: 10.3109/17477160902763333
|View full text |Cite
|
Sign up to set email alerts
|

The weight of opinion on childhood obesity: recognizing complexity and supporting collaborative action

Abstract: The shared social, cultural and psychological themes illustrate the complexity of childhood obesity as a public health issue, and the need for interventions and communications to take account of perceptions if they are to be relevant and effective. However, the commonality of views also indicates the potential for health professionals, schools, childcare, parents and young people to collaborate on community initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 29 publications
(42 reference statements)
3
51
0
Order By: Relevance
“…Some studies have documented that CCC caregivers can be aware and concerned about child overweight, showing positive attitudes and practices for promoting healthy feeding and active play. 6,7 In contrast, other studies have shown that CCC caregivers may discourage healthy behaviors and overlook opportunities for promoting PA. 8,9 Aside from previous studies, there is limited empirical evidence about the perceptions of CCC staff regarding their personal and organizational capacity for preventing child overweight. Therefore, this study aims to identify significant strengths, weaknesses, opportunities, and threats (SWOT) that are relevant to foster healthy feeding and PA, derived from the perceptions of five types of staff working at Mexican public CCC.…”
Section: Childcare Staff Perceptions For Preventing Overweightmentioning
confidence: 73%
See 3 more Smart Citations
“…Some studies have documented that CCC caregivers can be aware and concerned about child overweight, showing positive attitudes and practices for promoting healthy feeding and active play. 6,7 In contrast, other studies have shown that CCC caregivers may discourage healthy behaviors and overlook opportunities for promoting PA. 8,9 Aside from previous studies, there is limited empirical evidence about the perceptions of CCC staff regarding their personal and organizational capacity for preventing child overweight. Therefore, this study aims to identify significant strengths, weaknesses, opportunities, and threats (SWOT) that are relevant to foster healthy feeding and PA, derived from the perceptions of five types of staff working at Mexican public CCC.…”
Section: Childcare Staff Perceptions For Preventing Overweightmentioning
confidence: 73%
“…Studies conducted with health providers and teachers showed that health personnel needs appropriate training for having skills to participate effectively in weight management programs. 6,7 The availability of child feeding organizational manuals was identified as a key strength. According to Tolbert and Hall, 17 the explicit division of responsibilities, the understanding of how work should be done, and the description of interpersonal coordination, may foster accountability of the staff, strengthening organizational performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10,13,14] Several studies have shown that one of the barriers for health professionals when providing care to overweight/obese children is parent-related factors, such as the possibility that parents may become defensive and food may be seen as nurturing. [8,14,15] The low rate of measuring children's height and weight may be because it is a sensitive topic to discuss with parents, so GPs only weigh children when they are concerned or parents raise the issue. [14] GPs recognised that it was not easy to assist children and adolescents to manage their weight because they were not only dealing with individuals but with whole families.…”
Section: Introductionmentioning
confidence: 99%